Acute airway obstruction by laryngeal haematomas in acute immune thrombocytopenic purpura. Issue 846 (April 1996) - Aiken, T. C.; Collin, R. C.
Abstract : We report the case of a 79-year-old woman with acute immune thrombocytopenic purpura who spontaneously developed laryngeal haematomas which produced acute upper airway obstruction.